If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(24 + -1x) = 6 + -1x (24 * 3 + -1x * 3) = 6 + -1x (72 + -3x) = 6 + -1x Solving 72 + -3x = 6 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 72 + -3x + x = 6 + -1x + x Combine like terms: -3x + x = -2x 72 + -2x = 6 + -1x + x Combine like terms: -1x + x = 0 72 + -2x = 6 + 0 72 + -2x = 6 Add '-72' to each side of the equation. 72 + -72 + -2x = 6 + -72 Combine like terms: 72 + -72 = 0 0 + -2x = 6 + -72 -2x = 6 + -72 Combine like terms: 6 + -72 = -66 -2x = -66 Divide each side by '-2'. x = 33 Simplifying x = 33
| 14c-11=3(2c+7) | | 7=3-2+4x | | 6(w-2)+3w=24 | | (A+b)+3= | | 25xsquared-16=0 | | 3a+45+2a-10=180 | | .75n-2=-.875n+32 | | 3X-16=2N+18 | | 11x+10x=12x | | 5sinx+4cosx=0 | | 8c-(c-1)=9 | | -5x^2+39x+8=0 | | -24=3v+4(v+8) | | 4y+y+1=7y | | 3x-8+x+26=180 | | 6x-5(x-7)=-10 | | -24=3v+4(4+8) | | -5(r+7)=-87 | | 50+3x=x+82 | | -2=7(x-6)-2x | | 3x-7=5x-45 | | 9+8(5x+3)=-3-5(8x+3) | | -8x+9=-8x+5 | | -3.5x^2+42t+13=0 | | -3(2x-3)=4(x-7) | | 4(6x+2)=8(3x+1) | | .03x+.12(20)=.06+20+x | | 0.03=0.01+2.9 | | x^2-14x=-46 | | 46+12x=17x | | 1.2+12.2= | | 6x^2-38=0 |